Depth control of an unmanned underwater vehicle based on robust inversion and sliding mode variable structure control - Li, Fengyun; Huang, Shuang; Chen, Yuanbao; Zeng, Guanglong; Shi, Leixin; Zhan, Zihao (Journal of physics. Conference series, 2023)
This paper addresses the depth control problem of an underactuated Unmanned Underwater Vehicle (UUV) subject to model uncertainties and ocean current interference. A robust inversion sliding mode variable structure control method is proposed. First, a vertical-plane UUV depth control model is established. Then, the inversion control method is combined with the sliding mode variable structure control method to devise an inversion sliding mode control algorithm. In order to further improve the control system’s robustness against external environmental interference, a robust control methodology is introduced for the design of the depth controller. Simulation results demonstrate that the designed controller effectively addresses the issues of model uncertainties and ocean current interference, thereby enhancing the UUV’s depth control accuracy.